A relationship between the occurrence of the flight phase and the increase in velocity during V2 skating - Fujita, Z.; Ishige, Y.; Yoshioka, S.; Tauchi, K.; Iso, S.; Fukashiro, S.; Tsuchiya, J. (International Journal of Sport & Health Science, 2010)
Two types of profiles of ski reaction forces during V2 skating have been reported by previous investigations. One of the differences between these two profiles is in the existence of the "flight phase," i.e., the phase in between gliding and kicking off, in which the skis float above the snow while skiing. It has been suggested that the difference is caused by the skating velocity. The purpose of this study is to clarify whether or not there is a relationship between the occurrence of the flight phase and the increase in velocity during V2 skating. Seven elite male cross-country skiers performed two types of trials at different velocities (high and medium speeds). The high and medium speeds correspond to the competitive pace for a sprint race and a 10-km race, respectively. The kinematics was measured for each trial using two video cameras and a panning direct linear transformation technique. The flight phase was determined by the ski load data obtained from a sensor attached to the ski. No flight phase was confirmed during medium-speed skating, but a flight phase was confirmed during high-speed skating, indicating the existence of the flight phase is related to an increase in skating velocity. However, the hip- and knee-joint angles and the vertical displacement of the center of mass were not changed by an increase in skating velocity. These results suggested that the flight phase was a small change from the standpoint of kinematics, but it may cause changes in muscle activity since the leg muscle groups experience no ground reaction force.